1985
DOI: 10.1055/s-2007-999923
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Herpes Infection Complicated by Prolonged Premature Rupture of Membranes

Abstract: Three cases of patients who developed genital herpes virus infections after prolonged, premature rupture of membranes (PROM) at 28-31 weeks gestation are reported. These patients were expectantly managed without immediate intervention at the time of diagnosis of the genital herpes virus infection. In all three cases, there was no evidence of neonatal herpes virus infection at the time of delivery or before hospital discharge. The spectrum of decisions facing the physician managing a patient with prolonged PROM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…That study also indicated the increased risk of premature delivery in women with primary infections compared with those with recurrent outbreaks. 1 In this case, as in the case published by Ray et al, 3 ruptured membranes had been present more than 4 hours prior to discovery of the lesion.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…That study also indicated the increased risk of premature delivery in women with primary infections compared with those with recurrent outbreaks. 1 In this case, as in the case published by Ray et al, 3 ruptured membranes had been present more than 4 hours prior to discovery of the lesion.…”
Section: Discussionsupporting
confidence: 55%
“…None of these patients had reseal of membranes and all delivered prematurely. 3 The second case report in the literature describes a pregnancy complicated by ruptured membranes at 25.5 weeks with primary herpes infection managed by acyclovir. The infant delivered prematurely but never showed evidence of a herpetic infection.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on this topic is limited. Ray et al describes a case where amniocentesis on intact membranes returned positive for HSV and this resulted in a caesarean with the fetus unaffected [ 12 ], suggesting that fetal infection is more complex than just the presence of HSV in the intrauterine compartment. In the setting of unavoidable vaginal delivery in primary HSV, the risk of transmission and subsequent neonatal HSV is 41% [ 6 ].…”
Section: Discussionmentioning
confidence: 99%